ANALISA CAMPURAN BOTTOM ASH SEBAGAI BAHAN CAMPURAN AGREGAT HALUS DALAM PEMBUATAN BETON RINGAN (Universitas Muhammadiyah Palembang, 2022)
As a city develops, the demand for buildings increases. The implementation of construction increasinglyrequires very high costs due to rising prices and reduced raw materials. Utilization of Bottom Ash as amixture for making concrete has properties and shapes such as fine aggregate. Lightweight concrete is aspecial type of concrete designed for specific purposes. It generally has a density of less than 1900 kg/m3with a compressive strength of around 20 N/mm2. The purpose of using this Bottom Ash mixture isexpected to reduce the weight of concrete without reducing the compressive strength of the concrete. Thepercentage Bottom Ash mixture used was 10%, 20%, 30%, 40% and 50%. The results of the analysisshow that by using a mixture of 50% Bottom Ash, the specific gravity obtained reaches 1,738 kg/m3 with acompressive strength of 18.73 MPa while the maximum compressive strength is found in a 30% BottomAsh mixture with a specific gravity of 1,994 kg/m3 with a compressive strength of 39.12 MPa. From theabove analysis, it can be concluded that the more Bottom Ash used can reduce the specific gravity andstrength of the concrete. Meanwhile, the use of 30% Bottom Ash can increase the compressive strengthcompared to without using Bottom Ash by 29.53 MPa with a specific gravity of 2162 kg/m3.